Colchicine mutagenesis effects on the characteristics and correlation of the M2 variant population of rice varieties - SUNTAREE SURSON; SUPHASIT SITTHAPHANIT; JAKKAPAT PRACHACHIT; THARADOL JITJAK; KHUMPANAT WONGKERSON; TANAKORN RACHAPILA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Surson S, Sitthaphanit S, Prachachit J, Jitjak T, Wongkerson K, Rachapila T. 2025. Colchicine mutagenesis effects on the characteristics and correlation of the M2 variant population of rice varieties. Biodiversitas 26: 2355-2367. Rice is a self-pollinating plant. In conventional rice breeding, variability is created in rice by crossbreeding. The method of crossbreeding rice is complicated because it requires much expertise to breed. The method of creating genetic variability in rice using chemicals, such as colchicine, is simple. This study used colchicine-induced variability in rice seeds, after which M1 generation variant plants with awn seeds were selected to create an M2 population for selection and to study the variation in the characteristics and correlation of rice. The results of the present study revealed that the M2 population of each M1 variant differed from the parental plants that did not receive colchicine in many morphologies and yield components. In addition, the M2 variant populations of each rice variety also differed. The study of the correlation values revealed interesting results for many traits, such as when rice seeds with awns appeared, the percentage of pollination was low. High tillering resulted in a high number of panicles, full grains, full grain weight, and number of leaves, but it also reduced the stomatal width, plant height, leaf width, leaf length, first shoot diameter, and SPAD value. This study selected mutant rice lines that had potent agronomic characteristics to improve Thai rice varieties.